What drives the language proficiency of immigrants? - Ingo E. Isphording (IZA World of Labor, 2015)
Language proficiency is a key driver of immigrant integration. It increases job opportunities and facilitates social and political participation. However, despite its vital importance, many immigrants never reach adequate proficiency in the host country language. Therefore, insights into the underlying processes and associated factors are crucial for designing measures to improve language acquisition. Empirical evidence shows that immigrants differ in their ability to learn languages, in their experience of everyday language usage, and their incentives to learn host country languages. This offers a range of opportunities for public policy intervention.
Keywords: F22; J15; J24; J40; 330; immigrants; language proficiency; integration